2021
DOI: 10.1002/hep.32202
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylgalactosaminyltransferase‐4 protects against hepatic ischemia/reperfusion injury by blocking apoptosis signal‐regulating kinase 1 N‐terminal dimerization

Abstract: Background and Aims Ischemia‐reperfusion (I/R) injury is an inevitable complication of liver transplantation (LT) and compromises its prognosis. Glycosyltransferases have been recognized as promising targets for disease therapy, but their roles remain open for study in hepatic I/R (HIR) injury. Here, we aim to demonstrate the exact function and molecular mechanism of a glycosyltransferase, N‐acetylgalactosaminyltransferase‐4 (GALNT4), in HIR injury. Approach and Results By an RNA‐sequencing data‐based correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…MAPK signaling has been recognized as the major molecular event contributing to hepatic I/R injury ( Imarisio et al, 2017 ; Wang et al, 2017 ). During the hepatic I/R process, damage-associated molecular patterns (DAMPs) and ROS stimulation of hepatocytes can activate JNK and p38 signals that result in cellular inflammation and apoptosis ( Yang et al, 2019 ; Zhou et al, 2021b ). Importantly, MIF has been reported to function in regulating MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling has been recognized as the major molecular event contributing to hepatic I/R injury ( Imarisio et al, 2017 ; Wang et al, 2017 ). During the hepatic I/R process, damage-associated molecular patterns (DAMPs) and ROS stimulation of hepatocytes can activate JNK and p38 signals that result in cellular inflammation and apoptosis ( Yang et al, 2019 ; Zhou et al, 2021b ). Importantly, MIF has been reported to function in regulating MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TOLLIP interacts with ASK1 to increase its N-terminal dimerization, exacerbating hepatic I/R injury by activating the downstream JNK/p38 signaling pathway ( Yan et al, 2019 ). On the contrary, N -acetylgalactosaminyltransferase-4 protects against hepatic I/R injury by inhibiting ASK1 N-terminal dimerization and inactivating the ASK1-JNK/p38 axis ( Zhou et al, 2021 ). In brain I/R, ASK1 undergoes phosphorylation and activation through NO-induced dimerization of ASK1, thereby activating the JNK pathway ( Liu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these results, we observed that TXNIP overexpression activated ASK1, leading to a significant increase in the phosphorylation levels of JNK and p38 proteins, whereas TXNIP knockout or downregulation showed the opposite trend. Studies have found that the binding of N-acetylgalactosaminyltransferase-4 to ASK1 inhibits its N-terminal dimerization and subsequent phosphorylation, thus leading to strong inactivation of downstream JNK/p38 signaling [ 60 ]. Moreover, the therapeutic use of ASK1 inhibitors has been extensively described in several reviews [ 61 63 ].…”
Section: Discussionmentioning
confidence: 99%